Investigating the Impact of Financial Ratios, Good Corporate Governance and Digital Technology on Financial Distress in Banking Amid Inflation in the Digital Age - Nita Yura Roslina; Indah Damayanti; Sana Sholihah (JURNAL COMPUTECH & BISNIS, 2025)
This study examines the influence of financial ratios, good corporate governance (GCG), and digital advancement on financial distress in Indonesia's banking sector, with inflation as a moderating variable.  This research employs a quantitative methodology and panel-data regression analysis to examine 185 observations from 37 active banks over 2020-2024.  The analytical methods include descriptive statistics and panel-data regression with a fixed-effects model.  The model selection is based on Chow and Hausman tests, which indicate that the fixed-effect model is more appropriate for the data under analysis.  The analysis indicates a strong fit of the regression model, evidenced by an R-squared of 86.85% and statistically significant findings at the 1% level.  The primary findings indicate that the Loan to Deposit Ratio (LDR) positively affects financial stability, whereas the operational cost-to-operational income ratio (BOPO) negatively affects financial stability.  Inflation further intensifies the adverse impacts of non-performing loans (NPL) on financial distress.  This study underscores the significance of operational efficiency and meticulous risk management in sustaining financial stability in the digital age.  The findings underscore the imperative of operational efficiency, judicious credit risk management, and responsiveness to macroeconomic conditions to maintain financial stability in the banking sector in the digital era.  This study offers critical insights for banking sector stakeholders to understand the determinants of financial distress and implement strategic measures to improve bank financial stability amid evolving economic circumstances.